Auranofin, a thioredoxin reductase inhibitor, causes platelet death through calcium overload. (2nd January 2019) - Harper, Matthew T.
Abstract: Platelets are central to normal hemostasis and must be tightly controlled to prevent thrombosis. However, drug treatments that also affect platelets could lead to unwanted side effects on hemostasis or thrombosis. In this study, the effect of auranofin on platelets was tested. Auranofin, a gold-based thioredoxin reductase (TRXR) inhibitor, has been previously used in arthritis. Recently, auranofin and other inhibitors of the thioredoxin system have been proposed as novel anti-cancer therapies. TRXR is an important part of the antioxidant defenses in many cells that maintain intracellular proteins in their reduced state. TRXR activity in platelets could be completely inhibited by auranofin. Auranofin-treated platelets showed several features of cell death, including the inability to aggregate in response to thrombin, leakage of cytosolic lactate dehydrogenase, and surface exposure of procoagulant phosphatidylserine. Auranofin increased platelet reactive oxygen species production and intracellular calcium concentration. DTT, a sulfydyl reducing agent, and BAPTA-AM, which chelates intracellular calcium, prevented auranofin-induced phosphatidylserine exposure. These data suggest that TRXR is an important part of the platelet antioxidant defense. TRXR inhibition by auranofin triggers oxidative stress and disrupts intracellular calcium homeostasis, leading to platelet necrosis. The use of auranofin or other TRXR inhibitors could therefore lead to unwanted side effects.